Samuel Adams [large type] : a life - Stoll, Ira, 1972- (Thorndike Press large print biography, 2009)
In this stirring biography, Samuel Adams joins the first tier of founding fathers, a rank he has long deserved. With eloquence equal to that of Thomas Jefferson and Tom Paine, Adams helped ignite the flame of liberty and played a pivotal role in the events leading up to the bloody confrontation with the British. Gifted young historian and newspaperman Ira Stoll has written a gripping account of the man who was the Revolution's moral conscience.